Functionalized Iron Hydroxyapatite as Eco‐friendly Catalyst for NH3‐SCR Reaction: Activity and Role of Iron Speciation on the Surface. Issue 6 (16th January 2020) - Campisi, Sebastiano; Galloni, Melissa G.; Marchetti, Sergio G.; Auroux, Aline; Postole, Georgeta; Gervasini, Antonella
Abstract: Eco‐friendly catalysts have been obtained by functionalizing hydroxyapatite (HAP) with iron (Fe/HAP), according to three preparative methods ( flash ionic exchange, deposition‐precipitation, and impregnation). Fe/HAP samples ( ca . 2–7 wt.% Fe) have been tested in the reaction of NOx reduction by ammonia (NH3 ‐SCR) in the 120–500 °C interval with different NH3 /NO ratios (0.6–2) at fixed contact time (0.12 s). All Fe/HAP samples were active and selective in the NH3 ‐SCR reaction starting from ca . 350 °C. Better performances have been observed on catalysts prepared by deposition‐precipitation and impregnation (about 70 % of NOx conversion and selectivity to N2 higher than 95 % at 350 °C), where α‐Fe2 O3 and 3D ‐Fe2 O3 nanoclusters were present, as indicated by Mössbauer and UV‐Vis‐DR spectroscopies. On the opposite, paramagnetic Fe 3+ centres were the predominant species on samples prepared by flash ionic exchange. Further characterization techniques (XRPD, N2 ‐physisorption, acidity by NH3 adsorption, and H2 ‐TPR) have concurred to elucidate Fe‐sitting HAP and structure‐activity relationships. Abstract : NH3 ‐SCR catalysts : Hydroxyapatite can be functionalised with iron thanks to the presence of exchangeable Ca sites. The intrinsic amphotericity of HAP together with the redox activity of iron centres make Fe/HAP samples promising NH3 ‐SCR catalysts. The exchanged isolated Fe centres showed high N2 selectivity while aggregated α‐Fe2 O3 /HAP promoted NH3 overoxidation to N2 O.